- FEASIBILITY ANALYSIS OF A CERTIFIED DURIAN (Durio zibethinus) PLANT BREEDING BUSINESS IN A BREEDER GUIDED BY THE UPTD HORTICULTURE PARENT SEED GEDUNG JOHOR: FEASIBILITY ANALYSIS OF A CERTIFIED DURIAN (Durio zibethinus) PLANT BREEDING BUSINESS IN A BREEDER GUIDED BY THE UPTD HORTICULTURE PARENT SEED GEDUNG JOHOR - Fitri Yenti; Tri Martial; Zulheri Noer (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine the durian breeding business and analyze the feasibility of a certified durian (Durio zibethinus) plant nursery business in breeders assisted by UPTD Building Horticulture Parent Seeds. This research was carried out for 1 (one) month using a census method among captive farmers. Feasibility Analysis of Certified Durian (Durio zibethinus) Plant Breeding Business at the Breeder Assisted by UPTD Horticulture Parent Seeds Gedung Johor, shows that the average total production cost is IDR 174,451,854, while the revenue is IDR. 308,706,641 and income of Rp. 134,254,786 To find out whether the business is feasible or not, it can be used to analyze the business by calculating production costs, calculating revenue and analyzing the results then calculating the results using the R/C Ratio and B/C Ratio methods. The research results show that the R/C Ratio value is 1.58 and the B/C Ratio value is 0.58, production productivity is greater than the production BEP, namely 13,891 and the price received by the nursery owner is greater than the BEP price, namely Rp. 5,550. From the research results, it was concluded that the durian breeding business was profitable and worth pursuing. In developing the durian agribusiness, the support of the availability of quality seeds from superior varieties is critical to success. The reality in the field shows that the availability of quality seeds is still an obstacle, so many farmers still use random seeds.